2018
DOI: 10.1037/apl0000316
|View full text |Cite
|
Sign up to set email alerts
|

Changing abilities vs. changing tasks: Examining validity degradation with test scores and college performance criteria both assessed longitudinally.

Abstract: We explore potential explanations for validity degradation using a unique predictive validation data set containing up to four consecutive years of high school students' cognitive test scores and four complete years of those students' college grades. This data set permits analyses that disentangle the effects of predictor-score age and timing of criterion measurements on validity degradation. We investigate the extent to which validity degradation is explained by criterion dynamism versus the limited shelf-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Second, it is also possible that the criterion, career choice, changes over time (e.g., Dahlke, Kostal, Sackett, & Kuncel, 2018). In particular, individuals may gravitate toward more congruent environments over the course of their careers (Judge, Higgins, Thoresen, & Barrick, 1999; Schneider, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is also possible that the criterion, career choice, changes over time (e.g., Dahlke, Kostal, Sackett, & Kuncel, 2018). In particular, individuals may gravitate toward more congruent environments over the course of their careers (Judge, Higgins, Thoresen, & Barrick, 1999; Schneider, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the changing-person perspective is not what H1 is about, but it is important to keep in mind the fact that declining validity has more than one interpretation. We note however that the changing-task perspective gained compelling support from a recent study (Dahlke, Kostal, Sackett, & Kuncel, 2018) in which predictors (cognitive test scores) and performance criteria (college performance) were measured over multiple occasions rather than just once, thus making it possible to disentangle the two interpretations of declining validity. This study showed that the validity changes were mostly due to the time at which the criterion was measured and were barely influenced by the time at which the predictor was assessed.…”
Section: Which Abilities Dictate Success On the Task At Different Stamentioning
confidence: 91%
“…These data were nonrandomly sampled by virtue of being collected from schools that used the SAT as a selection device and that consented to provide students’ grade data to the College Board for research purposes. The database we analyzed has been used in other published research (e.g., Beatty et al, 2015; Dahlke et al, 2018, 2019; Higdem et al, 2016; Kostal et al, 2015; Shewach et al, 2017; Yu et al, 2016), but the present study reports unique analyses of these data and draws novel insights.…”
Section: Methodsmentioning
confidence: 99%